The Attraction Messages of Drama Movie Through FGD in Indonesia - Novi Andayani; Rd. Nia Kania Kurniawati; Heny Hayat (Magister Komunikasi Universitas Sultan Ageng Tirtayasa, 2020)
Tabula Rasa is a food theme story, which comes people's daily life. This movie is a story about Hans' life, a guy from Papua, with Mak, Natsir, and Parmanto from Padang, West Sumatera. A story about humanity and helping each other can be implemented in our life without seeing skin color, ethnic, and religious differences. This thesis uses message theory and message appeals theory with descriptive qualitative research and a Focus Group Discussion method as data collection. Researcher has found some messages containing rational, emotional, fear (threat), humor, reward, and motive appeals.Tabula Rasa adalah cerita tema makanan, yang datang kehidupan sehari-hari orang. Film ini adalah kisah tentang kehidupan Hans, seorang lelaki dari Papua, bersama Mak, Natsir, dan Parmanto dari Padang, Sumatera Barat. Sebuah kisah tentang kemanusiaan dan saling membantu dapat diimplementasikan dalam hidup kita tanpa melihat perbedaan warna kulit, etnis, dan agama. Tesis ini menggunakan teori pesan dan teori daya tarik pesan dengan penelitian kualitatif deskriptif dan metode Diskusi Kelompok Terfokus sebagai pengumpulan data. Peneliti telah menemukan beberapa pesan yang mengandung alasan rasional, emosional, ketakutan (ancaman), humor, hadiah, dan motif.